Erythrocyte sedimentation rate in heartworm naturally infected dogs “with or without” Leishmania infantum seropositivity: an observational prospective study - Cavalera, Maria Alfonsa; Gusatoaia, Oana; Uva, Annamaria; Gernone, Floriana; Tarallo, Viviana Domenica; Donghia, Rossella; Silvestrino, Marco; Zatelli, Andrea (Frontiers in Veterinary Science, 2024)
Canine heartworm disease by Dirofilaria immitis and canine leishmaniosis by Leishmania infantum (CanL) are both vector-borne diseases with frequently overlapping endemicity and able to trigger the acute phase response, being characterized by variations in acute phase proteins (APP). Recently, erythrocyte sedimentation rate (ESR), an indicator of inflammation, has gained attention in veterinary medicine, proving useful in several conditions that include CanL active forms in dogs. This study aims to evaluate ESR in heartworm-infected dogs, compare levels with heartworm-infected and L. infantum seropositive dogs as well as clinically healthy dogs, and assess correlations with other laboratory parameters. From October 2022 to January 2023, a prospective observational study was conducted enrolling heartworm-infected (Dirofilaria group) and heartworm-infected L. infantum seropositive (Dirofilaria/Leishmania group) animals subgrouped according to the CanL clinical form (Dirofilaria/Leishmania active and non-active groups). A group of clinically healthy dogs (control group) was also included. For each dog enrolled physical examination and laboratory tests (complete blood count, biochemical panel including APP, serum protein electrophoresis) were performed. Dirofilaria and Dirofilaria/Leishmania groups presented a significantly higher ESR level compared to healthy dogs. Dirofilaria/Leishmania active group had the highest ESR level among the groups considered. Dirofilaria/Leishmania non-active group had an ESR similar to the Dirofilaria group, but significantly higher and lower compared to the control and the Dirofilaria/Leishmania active group, respectively. A significant positive correlation between ESR and C-Reactive Protein has been found in all groups except for the Dirofilaria/Leishmania non-active group. In Dirofilaria/Leishmania active group a strong positive correlation between ESR and gamma globulins percentage as well as a strong negative correlation between ESR and albumin, albumin/globulins ratio were found. Overall, the ESR was confirmed to be an inflammation marker as well as a helpful disease index, being notably increased in heartworm-infected dogs affected by an active form of CanL.